The 4000-m team pursuit cycling world record: theoretical and practical aspects - Schumacher, Y. O.; Müller, P. (Medicine & Science in Sports & Exercise, 2002)
Due to constant competition conditions, track cycling can be accurately modeled through physiological and biomechanical means. Mathematical modeling predicts an average workload of 520 W for every team member for a new team pursuit world record. Performance in team pursuit racing is highly dependent on aerobic capacity, anaerobic skills, and aerodynamic factors. The training concept of the 2000 record-breaking team pursuit team was based on unspecific training of these qualities and periodical, short-term recall of previously acquired track specific skills. Aerobic performance was trained through high overall training mileage (29,000-35,000 km.yr-1) with workload peaks during road stage races. Before major track events, anaerobic performance, and track-specific technical and motor skills were improved through discipline-specific track training. Training intensities were monitored through heart rate and lactate field tests during defined track-training bouts, based on previously performed laboratory exercise tests. During pursuit competition, analysis of half-lap split times allowed an estimation of the individual contribution of each rider to the team's performance and thereby facilitated modifications in team composition to optimize race speed. The theoretically predicted performance necessary for a new world record was achieved through careful planning of training and competition schedules based on a concise theoretical concept and the high physiological capacities of the participating athletes.